Knowledge Of Princess Adolescent About Iron And Folic Acid Tablets Consumption With Anemia Events - Julaecha Julaecha; Safitri Safitri (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
Iron nutrition anaemia in adolescents is still a problem in Indonesia, where The need for iron and folic acid tablets in adolescents increases due to their growing period and having menstruation every month. Based on the results of Riskesdas 2018, 32% prevalence of anaemia occurs in adolescents as a result of a lack of food intake of iron sources. Various attempts were made to prevent and control anaemia but still Low awareness of young women about the importance of consuming iron and folic acid tablets as a measure to prevent anaemia. The result of a deficiency in haemoglobin levels causes symptoms of lethargy, fatigue and fatigue when doing activities which will have an impact on decreased concentration and learning achievement, and in the long term will affect the quality of human resources. The purpose of this study was to analyze the knowledge of young women about the consumption of iron and folic acid tablets with the incidence of anaemia in the female boarding school model STIKBA Jambi. Research design was cross-sectional, the population used in this study were young women in model dormitories, simple random sampling technique, the measuring instruments used were questionnaires and observation sheets as well as measuring instruments for haemoglobin (Hb) examination in the digital. The collected data were analyzed using the Chi-Square statistical test. The results showed that 65% of adolescents had high knowledge about the consumption of iron (Fe) tablets, and 80% had anaemia. The reasons for adolescents not taking iron (Fe) tablets included 50% because of the colour of the pills, 90% because of the smell of the drugs, 100% because of nausea, 75% because they don't feel any complaints of anaemia, and 65% because they have difficulty defecating. The results of the statistical analysis showed no relationship between knowledge of iron (Fe) tablet consumption and anaemia (p value> 0.05). Knowledge that the consumption of iron and folic acid tablets does not affect the incidence of anaemia and the reason young women do not consume iron and folic acid tablets is because of the side effects that arise after consuming the iron and folic acid tablets, and there are no symptoms of anaemia.